Partisipasi Masyarakat dalam Mengontrol dan Mengetahui Mekanisme Penggunaan Anggaran Dana Desa di Kecamatan Simalungun - Maria Ferba Editya Simanjuntak; Maslon Hutabalian (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Village Funds are Funds sourced from the State Revenue and Expenditure Budget allocated for villages to be used to finance government administration, development implementation, community development, and community empowerment. Village government is required to carry out governance in a transparent and accountable manner. Laws and Government Regulations have provided a clear legal umbrella so that the BPD does not need to hesitate in carrying out its function of supervising the performance of village heads. This study used qualitative research methods. Data collection was carried out through observation, in-depth interviews and discussions with related parties through snowball techniques. Data collection was carried out through observation, in-depth interviews and discussions with related parties through snowball techniques. The results showed: Village Community Kec. Panombeian Panei participates in the management of the village fund budget. Management of the village fund budget in the Village of Panombeian District Panei. How ever, the management is still inadequate due to unwise decisions, no budget transparency and a lack of accountability for the expenditure of the village fund budget itself.